Význam zaměstnaneckých benefitů se sportovním obsahem pro zlepšení životního stylu zaměstnanců ve vybraných firmách se sedavým zaměstnáním - Zemánková, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Cílem této práce je popsat význam zaměstnaneckých benefitů se sportovním zaměřením a navrhnout řešení pro zlepšení životního stylu a kvality života zaměstnanců ve vybraných firmách se sedavým zaměstnáním. Součástí práce bude osobnostní anketa a rozhovor. V závěru práce se objeví doporučení k realizaci benefitů vedoucích ke zlepšení zdravotního stavu a kvality života zaměstnanců ve vybraných firmách se sedavým zaměstnáním.

The aim of this paper is to address the importance of focusing employee benefits on promoting healthy lifestyle choices and exercise. The tools used will involve extensive research in a variety of fields, as well as employee surveys. The authors will focus on providing benefits recommendations and modifications to the benefits structure that will lead to the improvement of quality of life of employees with sedentary jobs.
The Importance of Employee Benefits with Sports Content to Improve the Lifestyle of Employees in Selected Companies with Sedentary Jobs
Keywords: Zaměstnanecké benefity; zaměstnanci; sedavé zaměstnání; zdravý životní styl; kvalita života.; Employee benefits; employees; sedentary job; healthy lifestyle; quality of life.